The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1590/s1516-18462012005000026
|View full text |Cite
|
Sign up to set email alerts
|

Formação acadêmico-profissional dos docentes fonoaudiólogos do estado da Bahia

Abstract: RESUMOObjetivo: analisar a formação do corpo docente graduado em Fonoaudiologia com vistas ao delineamento do perfil acadêmico-profissional do mesmo. Método: estudo observacional, descritivo e analítico, com abordagem quantitativa/ qualitativa, os dados de formação do universo de docentes fonoaudiólogos foram coletados por meio de questionário elaborado para esta finalidade e tratados com base na estatística descritiva. Resultados: a análise mostrou o universo de 62 docentes, distribuídos por quatro IES, major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
(19 reference statements)
2
3
0
1
Order By: Relevance
“…The female predominance in this study corroborates with data collected in other studies of teachers characterization conducted in Brazil [13][14][15] , which, among other things, pointing to the feminization in healthcare professions that is every day more noticeable 16,17 .…”
Section: Discussionsupporting
confidence: 90%
“…The female predominance in this study corroborates with data collected in other studies of teachers characterization conducted in Brazil [13][14][15] , which, among other things, pointing to the feminization in healthcare professions that is every day more noticeable 16,17 .…”
Section: Discussionsupporting
confidence: 90%
“…It must be highlighted that the subjects of this research are mostly females (88%) who graduated between 1990 and 2000. In other words, it is a relatively young population, corroborating articles in the literature that researched the profile of Brazilian SLH professors 20,21 .…”
Section: Discussionsupporting
confidence: 66%
“…Teixeira and collaborators (10) , on analyzing the egresses track record in Speech Language Therapy, identified that 94% of the professionals were from female gender. Another study (11) , that investigated the academic professional training of the speech language therapy teaching staff of Bahia state, revealed that 96.9% of them were from female gender. Presumably, the predominance of female gender is not only a characteristic of acting in Educational Speech Language Therapy, but of the profession as a whole.…”
Section: Resultsmentioning
confidence: 99%